Hallucinating Foucault - Duncker, Patricia 1951- (Vintage Books, a division of Random House, Inc., 1998)
An English student is so impressed by a book of philosophy that he travels to France to meet its author, now in an insane asylum. In describing the relationship which grows up between the two men, the novel looks at the bonds that are created between reader and writer, even though they never meet. A first novel.